ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Dea Fitria Kartikasari; Syafriont - (Jurnal Akademika, 2021)
The purpose of this report is to disclose the results of research aimed at finding out whether there is a significant difference in the financial performance of the company before and after the IPO (Initial Public Offering) of companies listed on the Indonesia Stock Exchange for the period 2015-2019. The population of this research is non-financial companies listed on the Indonesia Stock Exchange with the following criteria: 1) non-financial companies that conducted Initial Public Offering (IPO) in 2018, 2) Availability of financial reports for the two financial years prior to (2015-2016) and two financial years after (2018-2019) conducting an Initial Public Offering (IPO) or financial reports for 2015-2019. The analytical technique method used in this research is a quantitative method through the Non-Parametric Test (Wilcoxon Sign Test).The results showed that there was a significant difference in Current Ratio (CR) between before and after conducting an IPO. There is a significant difference in Debt to Equity Ratio (DER) between before and after conducting an IPO. There is a significant difference in Debt Ratio (DR) between before and after conducting an IPO. There is no significant difference in Net Profit Margin (NPM) between before and after conducting the IPO Keywords: Initial Public Offering, Current Ratio, Debt to Equity Ratio, Net Profit Margin